The Act of Impersonation in the Cinema and the Theatre - Mykhailo Barnych; Halyna Rozhko (Вісник Київського національного університету культури і мистецтв. Серія: Аудіовізуальне мистецтво і виробництво, 2020)
The purpose of this research is to identify and summarize the creative stages, components and sequence of impersonation in the cinema and the theatre. The research methodology is to apply the theoretical and analytical approach, in particular, while analyzing works and guidelines of theorists and practitioners of acting. The scientific novelty is an analysis of the sequence of the actor’s activities on the role in the cinema and the theatre. The main creative stages of the actor’s activities on the role are clarified. Based on the analysis of techniques and methods of impersonation, the relationship of the structural components that form the actor’s image in the cinema and the theatre is determined. Conclusions. The constituent elements of the act impersonation and its constituent elements are analyzed in the article. The acting creative process is divided into two main stages: preparation for the role-playing and the role-playing itself. The creative stage of preparation for the role-playing includes analysis and formation of the personality and characteristics of the particularities of the character, action analysis and play in the imagination. The second creative stage is the roleplaying in public, which means the creation by the actor of an act of experience based on external and internal role image, previously created independently and with the director. Structural components that form an actor’s personality are elaborated in detail. Gradual plan for impersonation has been developed and defined. The factors that influence successful role-playing are summarized.